2022
DOI: 10.1007/s00018-021-04038-8
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor family proteins are multitasking cytokines in tissue injury

Abstract: The family of macrophage migration inhibitory factor (MIF) proteins in humans consist of MIF, its functional homolog D-dopachrome tautomerase (D-DT, also known as MIF-2) and the relatively unknown protein named DDT-like (DDTL). MIF is a pleiotropic cytokine with multiple properties in tissue homeostasis and pathology. MIF was initially found to associate with inflammatory responses and therefore established a reputation as a pro-inflammatory cytokine. However, increasing evidence demonstrates that MIF influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 166 publications
(217 reference statements)
0
30
0
Order By: Relevance
“… 33 Multiple studies have found that the serum MIF concentration in patients with vitiligo vulgaris is significantly higher than the control group, and the serum MIF concentration in the active phase is higher compared with the stable phase. 6 , 15 , 34–36 Ma et al 37 and Garcia-Orozco et al 13 further found that MIF mRNA levels in skin lesions of patients with vitiligo were significantly increased, and serum MIF concentration and in situ expression were correlated with active non-segmental vitiligo, further suggesting that MIF plays a role in the pathogenesis of non-segmental vitiligo, especially in active patients. In our study, we found significant differences between patients and controls in terms of serum MIF levels.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“… 33 Multiple studies have found that the serum MIF concentration in patients with vitiligo vulgaris is significantly higher than the control group, and the serum MIF concentration in the active phase is higher compared with the stable phase. 6 , 15 , 34–36 Ma et al 37 and Garcia-Orozco et al 13 further found that MIF mRNA levels in skin lesions of patients with vitiligo were significantly increased, and serum MIF concentration and in situ expression were correlated with active non-segmental vitiligo, further suggesting that MIF plays a role in the pathogenesis of non-segmental vitiligo, especially in active patients. In our study, we found significant differences between patients and controls in terms of serum MIF levels.…”
Section: Discussionmentioning
confidence: 96%
“…Subsequently, MIF has been described as a proinflammatory factor with upstream regulatory roles in innate and adaptive immunity. 6 It has been shown to play a crucial role in several types of immune and autoimmune diseases. 7 , 8 MIF is mainly derived from macrophages and T cells and is secreted in response to several stimuli, including lipopolysaccharide (LPS), tumor necrosis factor (TNF)‐α, hypoxia, and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, MIF was first introduced as a proinflammatory cytokine, associated with inflammatory responses. However, recent evidence demonstrates that MIF influences cellular homeostasis, such as promotion of cellular survival, antioxidant signaling, and tissue repair (Song et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…19,[24][25][26] They also have an important pathogenic role in acute and chronic inflammatory conditions, cardiovascular diseases, lung diseases, neurodegenerative diseases, adipose tissue inflammation, and cancer, as summarized in previous review articles. [27][28][29][30][31][32][33][34][35][36][37][38][39][40] Curiously, both MIF and MIF-2 share a striking structural similarity and conserved N-terminal tautomerase pocket with a family of bacterial tautomerases, and display catalytic tautomerase activity in vitro [41][42][43] (Figure 1). Although the physiological relevance of this activity has yet to be elucidated, the existence of a catalytic pocket in the structure of these cytokines offers intriguing possibilities for the development of small molecule inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Following the molecular identification of the Mif gene 21–23 a quarter of a century later, today, MIF as well as its more recently described structural homolog D‐dopachrome tautomerase (D‐DT; now also termed MIF‐2), are known as multifunctional cytokines and chemokines with key roles in host immunity and homeostasis 19,24–26 . They also have an important pathogenic role in acute and chronic inflammatory conditions, cardiovascular diseases, lung diseases, neurodegenerative diseases, adipose tissue inflammation, and cancer, as summarized in previous review articles 27–40 . Curiously, both MIF and MIF‐2 share a striking structural similarity and conserved N‐terminal tautomerase pocket with a family of bacterial tautomerases, and display catalytic tautomerase activity in vitro 41–43 (Figure 1).…”
Section: Introductionmentioning
confidence: 99%